25 years of biophysics and functional diagnostics Department in Siberian State Medical University - M. B. Baskakov; L. V. Kapilevich (Бюллетень сибирской медицины, 2003)
Here is presented the history of biophysics and functional diagnostics Department creation in Siberian State Medical University, names of chair’s founders are given. The main directions of activity and scientific achievements are defined.